Unilateral pleural effusion as the sole clinical presentation of severe ovarian hyperstimulation syndrome: a systematic review. (1st February 2018) - Irani, Mohamad; Robles, Alex; Gunnala, Vinay; Chung, Pak; Rosenwaks, Zev
Abstract: The pathophysiology of isolated pleural effusion in ovarian hyperstimulation syndrome (OHSS) is not well defined. The objective of the current review is to delineate the pathophysiology, risk factors, preventive measures, and therapeutic options of isolated pleural effusion in severe OHSS. Major databases were searched until June 2016. Studies evaluating women who presented with pleural effusion as the sole extra-ovarian manifestation of severe OHSS were included. Data were extracted from 24 articles encompassing 30 reported cases. Values were expressed as mean ± SEM. Patients were young (31.5 ± 0.8 years old) and 29.1% of them were diagnosed with polycystic ovary syndrome. All the patients received human chorionic gonadotropin to trigger oocyte maturation. Estradiol level was 3110 ± 330 pg/mL on the day of the ovulatory trigger. Dyspnea was the presenting symptom in 86.6% of the patients. Pleural effusion was predominantly on the right side (80%). Ninety percent of the patients underwent thoracentesis (4332 ± 769 mL): 66.7% exudate and 33.3% transudate. Fluid initially accumulates in the peritoneal cavity then enters the pleural space due to the pressure gradient through the thoracic duct and diaphragmatic defects, which are more common on the right side. The risk factors, prevention, and management, which are also discussed in this review, are similar to those of severe OHSS.